Multimodality in CLIL assessment: implications for teacher assessment literacy - Liu, Jiajia Eve; Lo, Yuen Yi (Journal of multilingual and multicultural development, 2025)
Content and Language Integrated Learning (CLIL) features the integration of content learning and additional language learning. With the increasing recognition that representation and construction of content knowledge often involve multiple semiotic modes, it follows that the 'language' dimension in CLIL should be extended to a multimodal dimension. Researchers have been examining the affordance of multimodal resources in facilitating CLIL instruction, but little attention has been paid to CLIL assessment, where students' knowledge is assessed in their less proficient language. It is then worth exploring whether and how CLIL assessment allows students to mobilise multimodal resources to demonstrate their actual learning. Through in-depth individual interviews with 10 purposefully sampled secondary school CLIL teachers in Asian contexts and examining their assessment materials, this study investigates teachers' perceptions and practices of using multimodal resources in CLIL assessment. It is found that although teachers are aware of the affordance of multimodal resources in making assessment questions accessible to students and mediating students' content knowledge expression, teachers generally need more systematic knowledge and skills to design effective multimodal assessment tasks, develop multimodal assessment criteria, and provide feedback on students' multimodal production. These findings have important implications for CLIL assessment design and CLIL teacher assessment literacy.